EFEKTIVITAS BEBERAPA DOSIS BIOFUNGISIDA TRIKO SPPLUS TERHADAP JAMUR AKAR PUTIH (Rigidoprus lignosus) DI PEMBIBITAN BATANG BAWAH TANAMAN KARET (Hevea Brasuliensis) - Mardiana Wahyuni; Rahmad Habibi Nauli Harahap (Jurnal Agro Estate, 2017)
One of the main constraints on the cultivation of rubber plants are fungal root diseases (JAP) caused by R ligonosus. This Pathogen infecting plants in the nursery until since rubber plants. The disease control efforts have been carried out by means of chemical, technical culture and the use of biological agents. JAP is (soil borne disease) so it's not easy to control it. This research was conducted on the campus of STIP-AP Medan in January 2017 until June 2017, The study used a Randomized Design Group (RAK) factorial with 5 teatment and four replicatios. Use the trico SP plus with a dose of 50 g, 75 grams, 100 grams and 125 grams. The results of this research shown that the application of Biofungisida trico SP plus (125 grams) is the most effective treatment against pathogen Rigidoporus lignosus.